DEVELOPMENTAL PROGRAMMES AND POLICIES: A LOGIC MODEL APPROACH - Obuks Augustine EJOHWOMU; Morakinyo Kehinde ONIFADE; Babatunde ADEOYE (Journal of Construction Project Management and Innovation)
Drawing on a review of developmental policies and programmes since post-independence era, the programme logic model (PLM) is accepted as a framework for addressing the research aim, which is to develop a framework for the developmental future of Nigeria. A Logic Model based 6-way heuristic evaluation framework featuring: problems/issues, stakeholders’ needs/assets, desired results, influential factors, strategies, and assumptions, were developed. This approach provided a schematic play-out of the feasibility of the evaluated programmes, and weights were assigned to the proposed strategies and their respective expected outcomes by target respondents and Bayes’ theorem was applied to the respondents’ scores.The findings showed that the strategies for a modest growth in the agricultural sector are provision of incentives for cash crops farming, institutionalising of agricultural practices and re-introduction of agricultural insurance scheme. The current contribution of the agricultural sector to the total GDP is approximately 23.86%. A modest and continuous increase can be expected if the proposed three strategies are implemented on a 3-4-3 basis. The strategies for a modest growth in the manufacturing sector are hastening the development of the infrastructure master plan and public private partnership with successful primary sector players. The current contribution of the manufacturing sector to the total GDP is approximately 4.1%. A modest and continuous increase can be expected if the proposed two strategies are implemented on a 4-6 basis. The strategies for a modest growth in the education sector are core implementation of science and technology based educational policies and innovation and management. The current contribution of the education sector to the total GDP is approximately 3.58%. The implication, therefore, is that there is urgent need to encourage ‘productive’ infrastructural development, which will jump start a knowledge based economy in the medium-term, and a serviced based economy in the long-term.